Libâs at-Taqwâ: Identitas Muslimah antara Nilai Ilahiah dan Arus Sosial (Studi Komparatif Tafsir al-Mishbah dan al-Azhar) - Hurrahmi, Mifta; Kerwanto, Kerwanto; Nurbaiti, Nurbaiti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, Cianjur, indonesia, 2025)
This study examines the concept of libâs at-taqwâ in the Qur’anic perspective as a response to the social reality of Muslim dress in Indonesia, which is often understood merely in its outward form. The notion of piety clothing is frequently associated with ritual attire, yet in practice it has undergone meaning distortion, commercialization, and neglect of its spiritual essence. Using a thematic (mawḍū‘ī) tafsir approach through library research, this study focuses on Tafsîr al-Mishbâh by M. Quraish Shihab and Tafsîr al-Azhar by Hamka, particularly on Surah al-A‘râf/7:26. An analysis of their exegetical methods reveals different emphases: Quraish Shihab regards inner clothing as the true attire in Islam, while Hamka underscores outward clothing in accordance with the sharia as a concrete manifestation of inner piety. The Qur’an presents libâs at-taqwâ as a symbol of inner submission reflected through ethics, modesty, and spiritual awareness. This study highlights five forms of its implementation in modern life: as a symbol of self-awareness, an expression of moderation and aesthetic balance, a means of social and ethical protection, an Islamic identity in plural society, and a medium of da‘wah. Thus, libâs at-taqwâ must be understood holistically, integrating both inward and outward dimensions in harmony with Qur’anic guidance.